Analisis Perilaku Konsumtif Pembelian Album dan Photocard melalui Aplikasi X Pada Mahasiswa Sekolah Vokasi IPB Sukabumi - Nau, Naura Vania Ramadhani; David Rizar Nugroho (UHN IGB Sugriwa Denpasar, 2025)
The researcher aims to delve deeper into how app X or new media can be a contributing factor to consumer behavior in the purchase of K-pop merchandise, specifically albums and photocards. This study employs a qualitative-descriptive method involving in-depth analysis through interviews with key informants relevant to the research. The findings will be presented through a combination of text and visuals to illustrate the consumer behavior associated with the Korean Wave. The results demonstrate that app X, in particular, has influenced the purchasing behavior of K-pop fans due to its specialized features that facilitate purchasing, offer lower prices, and foster community interactions.